2022
DOI: 10.3389/fimmu.2022.826812
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Alterations in Depressive Disorder

Abstract: Depressive disorder is the most prevalent affective disorder today. Depressive disorder has been linked to changes in the white matter. White matter changes in depressive disorder could be a result of impaired cerebral blood flow (CBF) and CBF self-regulation, impaired blood-brain barrier function, inflammatory factors, genes and environmental factors. Additionally, white matter changes in patients with depression are associated with clinical variables such as differential diagnosis, severity, treatment effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 97 publications
1
9
0
Order By: Relevance
“…These results are consistent with reports that higher depressive dimensional scores were sometimes associated to fewer hospitalizations and fewer relapses at 3 and 5 years 97 , indicating better outcome for these patients, although poorer prognosis was also often reported 98 . Furthermore, the ROIs driving this correlation (CC, CR, CING) are often highlighted in WM DTI studies of depression 99 .…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with reports that higher depressive dimensional scores were sometimes associated to fewer hospitalizations and fewer relapses at 3 and 5 years 97 , indicating better outcome for these patients, although poorer prognosis was also often reported 98 . Furthermore, the ROIs driving this correlation (CC, CR, CING) are often highlighted in WM DTI studies of depression 99 .…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting observation in our present study was that besides the higher depression proportion, the AG group exhibited poorer WM microstructure integrity than the AA group, mainly in CC, internal capsule, corona radiata and fornix. These WM tracts have been reported to have decreased FA in MDD (91)(92)(93)(94). Vulser et al have investigated the association of subthreshold depression with WM microstructure alterations in adolescents and found that decreased FA in the anterior body and genu of CC in adolescents with subthreshold depression (95).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tractography is a visualization technique that reconstructs and maps the pathways of WM tracts in the brain based on DTI data ( 19 ). In particular, in MDD structural disruptions within WM tissue are reflected by decreased FA mainly localized in the corpus callosum (CC), cingulum and uncinate fasciculus ( 20 ). Moreover, reduction of FA has been found correlating with severity of depressive symptomatology ( 21 ) and MDD duration ( 22 ), probably explaining the impairments in general cognitive functioning often observed in these patients according to anatomical disruptions ( 23 ).…”
Section: Introductionmentioning
confidence: 99%